Perbedaan Tingkat Kesepian Mahasiswa Yang Tinggal Di Kost Dan Yang Tinggal Bersama Orang Tua/Keluarga Pada Program Studi Bimbingan Dan Konseling Universitas Sanata Dharma - Anggriani, Bernadeta Ria; Arswimba, Bernardinus Agus (Universitas Sanata Dharma, 2023)
This study aims: (1) To determine whether there is a difference in the level of loneliness of students who live in boarding houses and who live with parents/family (2) To determine the level of loneliness of students who live in boarding houses and (3) To determine the level of loneliness of students who live with parents/family. This type of research is quantitative with a comparative approach. The research subjects were students of the Guidance and Counseling Study Program as many as 60 students. The sampling technique is Non-probability with Purposive Sampling model. The data collection technique used a questionnaire with a modified Likert scale and was arranged based on aspects of the level of loneliness: (1) Emotional, (2) Social, (3) Cognitive, and (4) Behavior. The questionnaire was distributed to 60 samples and obtained 47 valid items with an Alpha-Cronbach reliability index of 0.939. Data analysis techniques using descriptive statistics and Independent Sample t-test or t-test. The results of this study indicate that there is no difference in the level of loneliness between students who live in boarding houses and those who live with parents / family because the p value is 0.304 0.05. The results of the categorization of the level of loneliness of students who live in boarding houses and who live with parents/family are both